Supercontinuum Generation in an Ytterbium-Doped Fiber Amplifier With Cascaded Double-Clad Passive Fiber Tapers - Chengmin Lei; Rui Song; Zilun Chen; Dongsheng Pu; Jing Hou (IEEE Photonics Journal)
Supercontinuum (SC) generation directly from an Ytterbium-doped fiber amplifier (YDFA) has many advantages such as high output power, low splicing loss, and high optical to optical conversion efficiency. However, the output spectrum can only extend to longer wavelength. We report a method to further extend the spectral range of SC generated in an YDFA at short wavelength direction by using cascaded double-clad passive fiber tapers. A 750 ps seed pulse at 1060 nm is amplified to 15.9 W and spectrally broadened from 1000 to 1600 nm in an YDFA system. Using this broadband source to pump cascaded double-clad passive fiber tapers, a 14.1 W SC source is obtained, covering 630 to 2000 nm, which is in an all-fiber and low-cost structure. It is found that, in fiber tapers, especially at the taper waist, the frequency shift rate of solitons increases significantly, and those red-shifted solitons are group-velocity matched to dispersive waves even in the red wavelength region. To our best knowledge, this is the first time there has been generation in tapered double-clad passive fiber.